2009
DOI: 10.1017/s0008423909990667
|View full text |Cite
|
Sign up to set email alerts
|

Losing Heart: Declining Support and the Political Marketing of the Afghanistan Mission

Abstract: Public support for Canada's military participation in Afghanistan became a hot-button issue in 2006. While there is some research investigating factors that influence support, and how it may differ among sub-groups of the population~Létourneau and Massie, 2005!, little attention has been given to how and why overall support changed over time~Kirton, 2007a!. In this paper, we look specifically at the interplay among three factors that led to an erosion of public support for Canada's military presence in Afghani… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
22
0
1

Year Published

2011
2011
2021
2021

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 24 publications
(25 citation statements)
references
References 16 publications
2
22
0
1
Order By: Relevance
“…Images of casualties personalize human war costs, and thus have powerful effects on viewers' perceptions: ''War casualty photographs may be the most emotionally arousing content available'' (Pfau et al 2006). These images make loss more personal, emotional, and salient, and thus function similarly to other cost-based factors previously found to accentuate individuals' reactions to casualties, such as geographic and social proximity (Gartner and Segura 2000;Gartner 2008b;Fletcher, Bastedo, and Hove 2009). As salient costs of war increase, individuals' support for a conflict and its leaders decreases.…”
Section: Contentmentioning
confidence: 69%
See 1 more Smart Citation
“…Images of casualties personalize human war costs, and thus have powerful effects on viewers' perceptions: ''War casualty photographs may be the most emotionally arousing content available'' (Pfau et al 2006). These images make loss more personal, emotional, and salient, and thus function similarly to other cost-based factors previously found to accentuate individuals' reactions to casualties, such as geographic and social proximity (Gartner and Segura 2000;Gartner 2008b;Fletcher, Bastedo, and Hove 2009). As salient costs of war increase, individuals' support for a conflict and its leaders decreases.…”
Section: Contentmentioning
confidence: 69%
“…2006). These images make loss more personal, emotional, and salient, and thus function similarly to other cost‐based factors previously found to accentuate individuals’ reactions to casualties, such as geographic and social proximity (Gartner and Segura 2000; Gartner 2008b; Fletcher, Bastedo, and Hove 2009). As salient costs of war increase, individuals’ support for a conflict and its leaders decreases.…”
Section: Theorymentioning
confidence: 70%
“…They process it [information] in light of their predispositions.'' 16 Roland Paris theorizes a similar attachment through the use of role theory to explain absence of change in public attitudes about foreign policy after the election of Stephen Harper in 2006. Paris found that the efforts of the Conservative government to change public predispositions toward international affairs and Canada's role on the world stage did not produce significant results.…”
Section: The Public Opinion/decision Maker Nexusmentioning
confidence: 99%
“…In recent years, problems have arisen because overt military missions have been couched in the rhetoric of peacekeeping, or, as Mair (2011) has noted, Canadian military missions have shifted from attempting to keep the peace to attempting to restore peace, often in the middle of violent conflicts (see also Fletcher et al 2009). Perhaps as a consequence of Canada's experience in Afghanistan and in prior missions (in particular, Somalia), the culture may value the ideas behind Canada as a peacemaker, but the public may be skeptical of turning words into deeds.…”
Section: Internationalism: Peacekeeping Foreign Aid and Human Rightsmentioning
confidence: 99%
“…The results displayed in Table 2 show that Conservatives were, on the whole, slightly more likely than others to disagree with the idea that Canada had overcommitted itself to peacekeeping operations (37 per cent vs. 31 per cent, x 2 ¼ 7.44; df ¼ 2; p , 0.03). One reason support for involvement in peacekeeping may be lower now than in times past is that the Canadian experience in Afghanistan featured both peacekeeping and combat activities (Fletcher et al 2009). It is an interesting and open question as to whether those who viewed Canada's role in Afghanistan as combat oriented have as a consequence become more skeptical of the country's future involvement in peacekeeping operations.…”
Section: Internationalism: Peacekeeping Foreign Aid and Human Rightsmentioning
confidence: 99%